The genetic architecture of anterior tooth morphology in a longitudinal sample of Australian twins and families. (September 2021) - Paul, Kathleen S.; Stojanowski, Christopher M.; Hughes, Toby; Brook, Alan; Townsend, Grant C.
Highlights: Crown morphology is moderately genetically integrated among deciduous teeth and among permanent teeth. Paired deciduous-permanent homologues are more strongly genetically integrated than traits expressed within dentitions. The same genes are recruited throughout development to yield morphologically similar phenotypes. When present in deciduous teeth, clinically problematic traits will likely be expressed in permanent replacement teeth. Abstract: Objective: This study presents a quantitative genetic analysis of human anterior dental morphology in a longitudinal sample of known genealogy. The primary aim of this work is to generate a suite of genetic correlations within and between deciduous and permanent characters to access patterns of integration across the diphyodont dental complex. Design: Data were recorded from casted tooth crowns representing participants of a long-term Australian twin and family study (deciduous n = 290, permanent n = 339). Morphological trait expression was observed and scored following Arizona State University Dental Anthropology System standards. Bivariate genetic correlations were estimated using maximum likelihood variance decomposition models in SOLAR v.8.1.1. Results: Genetic correlation estimates indicate high levels of integration between antimeres but low to moderate levels among traits within a tooth row. Only 9% of deciduous model comparisons were significant, while pleiotropy was indicated for one third of permanent trait pairs. Canine characters stood out as strongly integrated, especially in the deciduous dentition. For homologous characters across dentitions (e.g., deciduous i 1 shoveling and permanent I 1 shoveling), ∼70% of model comparisons yielded significant genetic correlations. Conclusions: Patterns of genetic correlation suggest a morphological canine module that spans the primary and secondary dentition. Results also point to the existence of a genetic mechanism conserving morphology across the diphyodont dental complex, such that paired deciduous and permanent traits are more strongly integrated than characters within individual tooth rows/teeth.